2020
DOI: 10.1111/jop.13003
|View full text |Cite
|
Sign up to set email alerts
|

“Search less, verify more”—Reviewing salivary biomarkers in oral cancer detection

Abstract: Oral squamous cell carcinoma is one of the commonest head and neck malignancies with approximately 350 000 cases reported annually and a mortality rate of 50% often attributed to late clinical presentation. Due to the close relationship between saliva bio‐fluid and tumour lesions, optimizing salivary biomarkers for disease detection and screening provides a major new research direction in diagnostic oral oncology. As inter‐tumour heterogeneity and intra‐tumour heterogeneity are common within oral cavity neopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 99 publications
(103 reference statements)
0
35
0
Order By: Relevance
“…Saliva is a biological fluid with features such as ease of sampling, cost-effectiveness, and non-invasiveness that make it a perfect diagnostic specimen, highlighting the importance of developing a method for early detection of OSCC based on validated salivary biomarkers [ 14 , 15 , 16 , 17 , 18 ]. Several well-designed studies recently reported on potential detection methods for oral cancer, suggesting analysis of salivary RNA and proteins [ 19 , 20 ], microRNAs [ 21 , 22 ], metabolites [ 23 , 24 ], glycoprotein [ 25 , 26 , 27 , 28 , 29 ], and the microbiome [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, as yet, no suitable biomarkers are regularly used in clinical practice for the management of oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Saliva is a biological fluid with features such as ease of sampling, cost-effectiveness, and non-invasiveness that make it a perfect diagnostic specimen, highlighting the importance of developing a method for early detection of OSCC based on validated salivary biomarkers [ 14 , 15 , 16 , 17 , 18 ]. Several well-designed studies recently reported on potential detection methods for oral cancer, suggesting analysis of salivary RNA and proteins [ 19 , 20 ], microRNAs [ 21 , 22 ], metabolites [ 23 , 24 ], glycoprotein [ 25 , 26 , 27 , 28 , 29 ], and the microbiome [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, as yet, no suitable biomarkers are regularly used in clinical practice for the management of oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, SARS-CoV-2 infection has been suggested to result in increased salivary amylase levels which may falsely indicate stress-induced body changes due to the sympathetic nervous system in an asymptomatic individual [17] , [20] . Likewise, protein biomarkers like peroxidase, peroxiredoxin-2, LDH, IL-6, and TNFα as well as microRNAs like let-7c and miR-27b, which have been previously linked to oral cancer and oral potentially malignant disorders, may result in false-positive findings in non-cancer individuals that suffer from COVID-19 infection [3] , [9] , [18] , [21] . Therefore, clinicians seeking to utilise salivary biomarkers presently may wish to consider a higher likelihood of lower validity due to possible COVID-19 infection.…”
Section: Consequences Of the Hypothesis/discussionmentioning
confidence: 99%
“…Incorporating saliva collection and analysis into the routine diagnosis and monitoring of systemic and oral conditions has become a promising research endeavour in recent times. The attractiveness of this biofluid stems from its inexpensive, easy, and repeatable collection that can be performed by untrained personnel with reduced risk of cross-infection [9] . Saliva is famed to comprise a hodgepodge of biological molecules that are secreted from major and minor salivary glands, Von Ebner’s glands, GCF, oral epithelium as well as contributions from respiratory and nasal secretion.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…Carcinomas of the head and neck, which collectively affect about 900 000 individuals globally and implicated in 4.7% of cancer‐related mortality annually, occur in an intricate anatomic region where relative difficulties may be encountered during invasive sampling and surgical intervention 3 . In consequence, biofluids including plasma, serum, saliva, and urine have been investigated with potential indicators to facilitate timely detection of primary and recurrent malignancies or predict treatment response described for most anatomic subtypes of head and neck tumors 1,4,5 . Notable is the fairly‐established practice of utilizing viral nucleic acids to screen and stratify nasopharyngeal and oropharyngeal carcinomas as well as circulating tumor cells for treatment response surveillance and metastasis prediction 6‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…Notable is the fairly‐established practice of utilizing viral nucleic acids to screen and stratify nasopharyngeal and oropharyngeal carcinomas as well as circulating tumor cells for treatment response surveillance and metastasis prediction 6‐11 . Simultaneously, the potential application of other molecular‐based diagnostic analytes using liquid specimen has gained attention with several promising biomarkers to serve as consensual or site‐specific cancer disease status classifiers documented to date 4,5 …”
Section: Introductionmentioning
confidence: 99%